Topography of carotid bifurcation: Considerations for neck examination - Sebastian Krystian Klosek (2018)
Clinical examination and surgical procedures require the knowledge of anatomical structures of such a complex area as neck, especially the developmental anomalies in vascular drainage may occur. The aim of this study was to describe the common carotid artery bifurcation to its surrounding structures to locate it properly by using external and internal landmarks. Measurements were performed on 43 Thai cadavers by the direct inspection method. Carotid bifurcation level was compared to the level of cervical vertebra, isthmus of thyroid cartilage, angle of mandible and origins of superior thyroid artery, and lingual artery. Most of carotid bifurcations were found at the level of C3, between C3 and C4, and C4 vertebra, as well as the tendency to lower position in men was noted. Measurements to the angle of mandible on the left sides were significantly different in studied groups (P = 0.02), also with lower position of bifurcation in men. The mean level of carotid bifurcation was approximately 6 mm above ITC, which literally is at the level of the superior border of thyroid cartilage. Moreover, in four cases, common carotid artery did not bifurcate bilaterally, and in four cases, no bifurcations were found at the right side of neck. Further, many superior thyroid arteries originated from common carotid artery. To sum up, during the clinical procedures, the level of thyroid cartilage is mostly advised to follow to locate the carotid sinus. Further, the described variations in topography of carotid bifurcation and arteries origins may have important clinical implications. © Springer-Verlag 2008.